Oligogenic Inheritance Underlying Incomplete Penetrance of PROKR2 Mutations in Hypogonadotropic Hypogonadism - Mkaouar, Rahma; Abdallah, Lamia Cherif Ben; Naouali, Chokri; Lahbib, Saida; Turki, Zinet; Elouej, Sahar; Bouyacoub, Yosra; Somai, Maali; Mcelreavey, Kenneth; Bashamboo, Anu; Abdelhak, Sonia; Messaoud, Olfa (Frontiers in Genetics, 2021)
The role of the prokineticin 2 pathway in human reproduction, olfactory bulb morphogenesis, and GnRH secretion is well established. Recent studies have highlighted the implication of di/oligogenic inheritance in this disorder. In the present study, we aimed to identify the genetic mechanisms that could explain incomplete penetrance in Hypogonadotropic Hypogonadism. This study involved two unrelated Tunisian patients with HH, which was triggered by identifying a homozygous p.(Pro290Ser) mutation in the PROKR2 gene in a girl (HH1) with Kallmann Syndrome. The functional effect of this variant has previously been well demonstrated. Unexpectedly, her unaffected father (HH1P) and brother (HH1F) also carried this genetic variation at a homozygous state. In the second family, we identified a heterozygous p.(Lys205del) mutation in PROKR2 both in a male patient with normosmic IHH (HH12) and his asymptomatic mother. Whole Exome Sequencing in the three HH1 family members allowed the identification of additional variants in prioritized genes. We then carried out digenic combinations prediction using the ORVAL software. For HH1, we found the highest number of disease-causing variant pairs. Notably, a CCDC141 variant (c.2803C>T) was involved in 18 pathogenic digenic combinations. The CCDC141 variant acts in an autosomal recessive inheritance mode, based on the digenic effect prediction data. For the second patient (HH12), prediction by ORVAL allowed the identification of an interesting pathogenic digenic combination between DUSP6 and SEMA7A genes, predicted as ‘dual molecular diagnosis’. The SEMA7A variant (p.(Glu436Lys) is novel and predicted as a VUS by Varsome. Sanger validation revealed the absence of this variant in the healthy mother. We hypothesize that disease expression in HH12 could be induced by the digenic transmission of the SEMA7A and DUSP6 variants or a monogenic inheritance involving only the SEMA7A VUS if further functional assays allow its reclassification into pathogenic. Our findings confirm that homozygous loss-of-function genetic variations are insufficient to cause KS, and that oligogenism is most likely the main transmission mode involved in CHH.